Building Social Trust: A Human Capital Approach - HUANG, Fali (Institutional Knowledge at Singapore Management University, 2007)
Much evidence suggests individuals di¤er in their predisposition to cooperate, which is essentially a component of human capital. This paper examines the role of individual cooperative tendencies and their interactions with institutions in generating social trust; it also endogenizes cooperative tendencies using a human capital investment model. Multiple equilibria and ine¢ ciencies exist due to positive externalities. An innovative …nding is that, when institutions are more e¤ective in punishing defecting behaviors, more people invest in cooperative tendencies and hence the endogenous social trust is higher, though the equilibrium cooperative tendencies are lower. This paper provides a plausible explanation for many empirical and experimental results